Do knowledge management systems motivate and satisfy the academic staff in higher education Institutions? (Journal of Applied Learning and Teaching, 2022)
Higher education knowledge management has three goals: improving task quality and efficiency, training human resources at all operational levels, and expanding an organization’s field knowledge base to enhance the organization’s knowledge or intellectual investment. This research aimed to elucidate the effect of knowledge management on teaching motivation and academic staff satisfaction in Vietnamese universities. The purpose of this study is to establish a clear relationship between knowledge management and teaching motivation and academic staff satisfaction; three dimensions of knowledge management systems, namely knowledge acquisition, knowledge dissemination, and knowledge utilization, all of which contribute to increased teaching motivation and academic staff satisfaction when knowledge management systems are implemented. The quantitative research technique was utilized to gather data in this study by surveying 381 professors using a questionnaire. SPSS 22.0 and SmartPLS software were used to process data obtained via survey professors engaged in teaching. Managerial implications for knowledge management systems have been suggested to increase academic staff satisfaction and teaching motivation.